Rise of palliative care in cardiology - Dei Santi, Daniel Battacini; Pêgo-Fernandes, Paulo Manuel (São Paulo Medical Journal, 2025)
Cardiovascular diseases (CVDs) are among the most prevalent and widespread diseases worldwide, regardless of gender, age, ethnicity, or social class, and are the leading cause of death, especially in older age groups. Cardiology has developed exponentially over the last few decades, with scientific and technological advances improving disease control and increasing longevity. Therefore, a gradually increasing number of patients should be living with CVD.